ANALYSIS OF LEGAL CERTAINTY, LEGAL PROTECTION AGAINST CANCELLATION OF REGISTERED MARKS (STUDY OF DECISION NUMBER 03/PDT.SUS-MEREK/2015/PN NIAGA MEDAN) - Lenny Mutiara Ambarita (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The purpose of this research is to analyze legal certainty and legal protection against cancellation of registered trademarks (Decision Study Number 03/Pdt.Sus-MEREK/2015/PN Niaga Medan). The type of research used in writing this thesis is normative juridical research. Normative juridical research, "is a research conducted by examining literature or secondary data such as laws and regulations, legal theory, and opinions of leading legal scholars". The data used as material for the analysis of this thesis research is secondary data, namely the data in this study consists of primary legal materials, secondary legal materials and tertiary legal materials. The analysis was carried out by means of qualitative analysis, namely an analysis that uses normative (juridical) aspects through a method that is descriptive in nature, an analysis that describes an overview of the legal materials obtained and links them to one another to obtain a general conclusion. The results of the study show that the implementation of trademark registration must be based on the good intentions and honesty of the trademark registrar to register their mark without any hidden intention to hitchhike or knock over other people's marks in order to gain the maximum economic advantage. Good faith in trademark registration includes an understanding in a subjective sense whereby a trademark registrant must have good and honest intentions in his heart to register his mark solely to protect said mark from fraudulent actions by other parties. Thus it can be said that in the case of trademark registration by the trademark registrant, the intention, both subjectively and objectively, must comply with the provisions of the laws and regulations that apply in the field of marks. In order to fulfill the legality of trademark ownership, the trademark registrant must have a trademark certificate, because a trademark certificate is proof that the mark has been registered and also as proof of ownership. By having legality, the brand owner will get legal protection which is a guarantee to process if there is a violation of the mark..